2014
DOI: 10.18632/oncotarget.1811
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of reactive resistance and early disease progression during chemotherapy plus bevacizumab treatment for colorectal carcinoma

Abstract: Molecular markers for predicting or monitoring the efficacy of bevacizumab in patients with metastatic colorectal cancer (mCRC) remain to be identified. We have now measured the serum concentrations of 25 angiogenesis-related molecules with antibody suspension bead array systems for 25 mCRC patients both before and during treatment in a previously reported phase II trial of FOLFIRI chemotherapy plus bevacizumab. The serum concentration of vascular endothelial growth factor–A (VEGF-A) decreased after the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 29 publications
4
40
1
Order By: Relevance
“…Thereby, our exploratory analysis demonstrated that levels of other angiogenic factors at baseline did not correlate with outcome, while interestingly they could be changed under administration of BEV. In previous reports, blood concentrations of several angiogenic factors significantly increased prior to radiological disease progression or were higher in responders compared to non‐responders at various points during BEV treatment . Such phenomena are consistent with our results: decrease in serum IL‐8 levels is expected to achieve a better clinical outcome as shown in the CCL5 rs2280789 G/G variant, and a modest increase of PlGF marked in any CCR5 rs1799988 T allele than the C/C is also expected to provide a better outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Thereby, our exploratory analysis demonstrated that levels of other angiogenic factors at baseline did not correlate with outcome, while interestingly they could be changed under administration of BEV. In previous reports, blood concentrations of several angiogenic factors significantly increased prior to radiological disease progression or were higher in responders compared to non‐responders at various points during BEV treatment . Such phenomena are consistent with our results: decrease in serum IL‐8 levels is expected to achieve a better clinical outcome as shown in the CCL5 rs2280789 G/G variant, and a modest increase of PlGF marked in any CCR5 rs1799988 T allele than the C/C is also expected to provide a better outcome.…”
Section: Discussionsupporting
confidence: 92%
“…30 Interleukin 8 is a proinflammatory cytokine related to ocular angiogenesis and to increased vascular permeability. 31 In an investigation of biomarkers related to cancer resistance to bevacizumab, Hayashi et al 32 detected higher serum concentrations of interleukin 8, angiopoietin 2, and VEGF-C in nonresponders compared with responders to bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies reported the correlation between tumor-related markers in blood association with treatment efficacy by chemotherapy [25, 26]. Hayashi et al demonstrated that an early increase in the serum VEGF-A concentration after the initial decrease is a potential predictive marker of poor tumor response in the second-line FOLFIRI plus bevacizumab for metastatic CRC patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al demonstrated that an early increase in the serum VEGF-A concentration after the initial decrease is a potential predictive marker of poor tumor response in the second-line FOLFIRI plus bevacizumab for metastatic CRC patients [26]. However, a different treatment-line setting and a blood collection point should be discussed, i.e.…”
Section: Discussionmentioning
confidence: 99%